2014
DOI: 10.1111/ics.12180
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a multiple emulsion, liposomes and a microemulsion gel on sebum, skin hydration and TEWL

Abstract: All produced vehicles were proven to remain physically stable over the duration of this study. The used multiple emulsion showed very skin-friendly properties by increasing sebum and skin hydration. Likewise, the liposomal pre-formulation exhibited no negative effects. On the contrary, the investigated microemulsion gel seemed to have skin dehydrating and TEWL increasing features. However, the multiple emulsion as well as liposomes was identified to be well-tolerated vehicles for skin which might qualify them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 13 publications
2
20
0
1
Order By: Relevance
“…We compared skin biophysical parameters and bacterial communities in facial cheek skins with different hydration levels (HHG and LHG). TEWL in HHG was lower than that in LHG (Figure ), in accordance with a previous study (Mahrhauser, Nagelreiter, Baierl, Skipiol, & Valenta, ). Facial skin roughness was not significantly different depending on the skin hydration level (Figure ).…”
Section: Discussionsupporting
confidence: 92%
“…We compared skin biophysical parameters and bacterial communities in facial cheek skins with different hydration levels (HHG and LHG). TEWL in HHG was lower than that in LHG (Figure ), in accordance with a previous study (Mahrhauser, Nagelreiter, Baierl, Skipiol, & Valenta, ). Facial skin roughness was not significantly different depending on the skin hydration level (Figure ).…”
Section: Discussionsupporting
confidence: 92%
“…Measurement of TEWL parameter is often used to estimate the changes in skin barrier function . The obtained results showed that both samples (EM and PL) led to a little increase in the value of TEWL after 14 or 28 days compared to baseline, but without statistical significance ( P > 0.05).…”
Section: Resultsmentioning
confidence: 92%
“…TEWL value is regarded as one of the most important parameters for skin barrier function. [15] TEWL is a measure of the flux density of condensed water diffusing from the deeper highly hydrated layers of the dermis and epidermis to the skin surface. TEWL values are affected by the state and function of the stratum corneum (SC).…”
Section: Discussionmentioning
confidence: 99%